ANALISIS PANDANGAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Sri Wahyuni; Fitri Puji Rahmawati; Anik Gufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to analyze the views of teachers who directly implement the independent curriculum in elementary schools. By using a qualitative approach. The research subjects were class I, II, IV and V teachers at SDN 01 Mojoroto. Data was collected using interview, observation and documentation techniques. Data were analyzed using the Miles and Huberman technique, namely: data reduction, data presentation, and drawing conclusions. The research results show that teachers view positively and appreciate the flexibility and innovation opportunities offered by the independent curriculum. However, they also face challenges such as: understanding the curriculum, availability of resources or teaching materials, and administrative burden. With continued support from various parties, the challenges faced by teachers in implementing the independent curriculum can be overcome. Teachers' positive views on the implementation of the independent curriculum have an impact on improving the quality of learning. The students' responses were very positive, they were more enthusiastic in following the lessons because the learning method was more interactive and fun.